Control interno de las cuentas por cobrar en la empresa "Campo-Track S.A" de la parroquia Isla de Bejucal - cantón Baba en el período 2021. - Carrasco Elizondo, Laiza Margarita (2022)
The internal control system within an organization is essential to verify a perfect functioning in all the activities that are carried out, in addition to ensuring the well-being of the company since it is important, because the system allows monitoring avoiding losses in capital due to scams or errors on the part of the staff. The company avoids losing its assets due to fraud, as well as the accounts receivable of some clients, for this it must have an excellent administrative management that can provide security and confidence. When internal control is executed within the company, it allows all departments to be evaluated together and to see how well the controls are working on the tasks to be carried out. Communication is a key basis to achieve objectives, an institution that has a good relationship between workers will be able to generate assets and avoid mistakes that can cause financial losses. The efficiency and effectiveness of the accounting, administrative and financial systems determine the success of a company. Organizations that manage to obtain margins above the commercial average are considered successful. Higher income often means greater financial success, because they make the most of their income. In the Campo-Track company, the most relevant aspects and most significant findings of the investigation, obtained from the application of the COSO model through the application of a questionnaire and internal control evaluation matrix to the administrative and collection environments, It is concluded that the efforts and resources that the company allocates for the internal control procedures that are the object of this study, are mainly focused on supervising that the corresponding collection is carried out and that the person in charge of collections fulfills his functions such as notification to clients. and issuance of fortnightly reports.